TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP KREDIT USAHA RAKYAT (KUR) SYARIAH PADA PEGADAIAN SYARIAH CABANG PASAR RENTENG PRAYA LOMBOK TENGAH - Angriani, Parida (Fakultas Agama Islam, 2024)
UMKM have great potential in economic development in Indonesia. However, there are still many UMKM sectors that face problems in developing their businesses, namely limited financial problems in obtaining additional capital. Currently, many financial services offer capital loans, one of which is the Renteng Sharia Pawnshop institution which distributes Super Micro People's Business Credit (KUR). Because the distribution of Super Micro KUR has only just begun to be distributed, it is necessary to examine everything related to distribution practices, namely the process/procedures, terms, contracts, conditions and whether the problem resolution process is in accordance with the economic system in sharia economic law. This research uses a field/empirical approach with qualitative research methods that describe the objects or subjects studied in depth using empirical evidence obtained through interviews, observation, documentation of reality in the field. The research results show that credit in Islam is permissible because originally there was no text that forbade it. Most scholars say yes. The distribution of Super Micro KUR at Renteng Syariah Pegadaian does not contain anything that is detrimental to both parties and is in accordance with sharia economic law because it has implemented the principles of justice ('adl), balance (tawazun), benefit (maslahah), and does not contain elements of gharar (vagueness/obscurity). vaguely, maysir (gambling), usury, dzulm (tyranny), risywah (bribery), and other haram objects.